The Interaction Between Text Modality and the Learner’s Modality Preference Influences Comprehension and Cognitive Load - Lehmann, Janina; Seufert, Tina (Frontiers in Psychology, 2020)
This study investigates the aptitude–treatment interaction between text modality and learners’ modality preference on learning outcomes and cognitive load, which is currently a point of controversy. The Meshing Hypothesis postulates there are better learning outcomes when the modality of a learning environment matches the learner´s preference. However, previous research supporting the Meshing Hypothesis shows methodological issues. Therefore, clear empirical support is needed. We tested 42 learners in a between-subject design: Their preferences were either auditive–ambiguous or visual, and half of each preference group randomly learned either with an auditive or a visual text. As expected, we did not find any main effects, but a significant interaction between the text modality and the learner´s preference for comprehension outcomes, extraneous cognitive load, and germane cognitive load. Specifically, learners with a preference for visual texts benefit from learning with their preferred modality, they showed higher comprehension scores and less extraneous load when learning from a visual text. Auditive–ambiguous learners showed almost equal results with both text modalities. This might be explained by the fact that most texts in everyday life are presented visually, and therefore learners with an auditive preference needed to develop appropriate reading strategies. Thus, our results partly support the Meshing Hypothesis.